The impact of the COVID-19 pandemic on accounting information systems and organizations’ performance - Gomes, Pedro (2023)
This paper empirically examines the impact of COVID-19 on accounting information systems and organizations' performance. It follows a quantitative approach. For data collection, an online questionnaire was developed and tested. The final version of the questionnaire was applied to the 2556 largest companies in Portugal. The 3 research hypotheses under study were tested with 101 valid answers. The results reveal a high rate of implementation of accounting and performance measurement instruments during the COVID-19 pandemic. Regarding the dynamics of the updates of organizations’ performance measurement systems, the impact of the COVID-19 pandemic was confirmed and described as primarily positive. In turn, the performance of the companies was negatively impacted by the COVID-19 pandemic. This study contributes to a better understanding of the role of accounting and performance instruments in organizations under a high level of organizational uncertainty.